Important roles of protein tyrosine phosphatase PTPN12 in tumor progression. (June 2019) - Lee, Chaelin; Rhee, Inmoo
Graphical abstract: Abstract: Protein tyrosine phosphatases (PTPs), which are ubiquitously expressed in hematopoietic and non-hematopoietic cells, are critical for regulating cell proliferation as well as differentiation in the physiology of multicellular organisms. PTPs regulate the intracellular signaling mechanism of immune cells via dephosphorylation of multiple targets and are associated with the onset of various autoimmune diseases through genomic alterations. PTPs also affect disease through their role in innate and/or acquired immunity. By modulating multiple substrates, PTPN12, a member of the proline-, glutamic acid-, serine- and threonine-rich (PEST) family of PTPs, is an important regulator of cell migration and adhesion. According to its newly identified roles and functions, PTPN12 is considered a promising therapeutic target against critical diseases, including cancer, diabetes, metabolic disease and autoimmune diseases. In this review, we provide an overview of PTPs and discuss the critical roles of PTPN12/PTP-PEST in tumor progression.